Pengaruh Latihan Target Sasaran Untuk Meningkatkan Kemampuan Shooting Free Throw Bola Basket Pada Ekstrakurikuler SMP Negeri 1 Welahan - Dhimas Dwi Prasetyo; Bertika Kusuma (Journal of Physical Activity and Sports (JPAS), 2020)
The research objective was to see the increase in the ability to shoot targets at basketball extracurricular activities at SMP Negeri 1 Welahan. The research method used is quantitative research methods with a type of quasi-experimental research method. The study population was the female basketball extracurricular members at SMP Negeri 1 Wagian using a purposive sampling sample of 20 extracurricular participants. This type of research with a quantitative approach using the pretest posttest control group design. The data analysis method used difference test with paired sample-t-test with a significant level of 5%. Calculation of data obtained from 10 class VIII students of SMP Negeri 1 Welahan (experimental class) and 10 students of class VIII at SMP Negeri 1 Welahan (control class), it is known that the Kolmogorov –smimov normality test of the pretest experimental class sig 0.263, posttest experimental class sig. 0.177, pre-test control class sig. 0.410, posttest control class sig. 0.421. The homogeneity test of the students' training results obtained sig. 0.809. Based on the output pair 1 of the experimental class, the sig value is obtained. (2-tailed) 0.000, and the output pair 2 control class sig value. (2-tailed) 0.619. The conclusion of this research is to increase the results of shooting through the application of the target game model. The increase in the experimental class was 28.8%. 2.4% increase in Control Class. So, the use of target practice can improve the ability to shoot free throws and it is hoped that the trainer can provide target practice to improve the shooting relationship. Keywords: Targets, Shooting Free Throw, Basketball Abstrak Tujuan penelitian ini untuk mengetahui peningkatan kemampuan shooting free throw melalui target sasaran pada ekstrakurikuler bola basket di SMP Negeri 1 Welahan. Metode penelitian yang digunakan yaitu metode penelitian kuantitatif dengan jenis metode penelitian quasi eksperimen. Populasi penelitian ini adalah peserta ekstrakurikuler bola basket putri di SMP Negeri 1 Welahan menggunakan sampel purposive sampling sebanyak 20 peserta ekstrakurikuler. Jenis penelitian dengan pendekatan kuantitatif menggunakan desain Pretest posttest control group design. Metode analisis   data menggunakan uji perbedaan dengan paired sample-t-test dengan taraf signifikan5%. Penghitungan data diperoleh dari 10 siswa kelas VIII SMP Negeri 1 Welahan (kelas eksperimen) dan 10 siswa kelas VIII SMP Negeri 1 Welahan (kelas kontrol) diketahui tes normalitas kolmogorov –smimovnilai pretest kelas eksperimen sig. 0,263, posttest kelas eksperimen sig. 0,177, pretest kelas kontrol sig. 0,410, posttest kelas kontrol sig. 0,421. Uji homogenitas hasil latihan siswa diperoleh sig. 0,809. Berdasarkan output pair1 kelas eksperimen diperoleh nilai sig. (2-tailed) 0,000, dan output pair 2 kelas kontrol diperoleh nilai sig.(2-tailed) 0,619. Simpulan penelitian ini adalah adanya peningkatan hasil shooting free throw melalui penerapan model permainan target sasaran. Kenaikan kelas eksperimen sebesar 28,8%. Kenaikan Kelas Kontrol sebesar 2,4%. Jadi,penggunaan latihan target sasaran dapat meningkatkan kemampuan shooting free throw dan diharapkan pelatih dapat memberikan latihan target sasaran untuk meningkatkan akurasi shooting. Kata kunci: Target sasaran, Shooting Free Throw, Bola Basket